DAMPAK PENERAPAN PERUBAHAN SISTEM PENDIDIKAN SMA DALAM ANIME KOKURIKO-ZAKA KARA - Fajria Noviana; Budi Mulyadi (Diponegoro University, 2018)
(Title: The Impact of Implementing Changes in High School Education System in Kokuriko-zaka Kara Anime) This anime tells story about Konan High School students who fight to protect an old building, which has become a center for their activities, from destruction by school owner. The purpose of this paper is to explain the impact of implementing changes in Japan’sHigh School education system at Showa period which described in this anime. Dialectical method is used to analyze social factors which contained in this anime as a litperiodry work. This method combines the results of analysis with facts of fiction found in litperiodture and facts in society. Stalcup’s theory of education is used to analyze how Japan’s educational system affecting those high school students. The results are: 1) changes in education system succeeded in making students to be more active, creative, brave, hard working, and work in team; 2) changes in education system succeeded in increasing student’s learning passion and adding insight and understanding of science; 3) changes in education system succeeded in improving Japanese education standard and providing same opportunities for boys and girls to have higher education.